2020
DOI: 10.3389/fimmu.2020.02120
|View full text |Cite
|
Sign up to set email alerts
|

The TLR4-MyD88 Signaling Axis Regulates Lung Monocyte Differentiation Pathways in Response to Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae is the main cause of bacterial pneumonia, a condition that currently produces significant global morbidity and mortality. The initial immune response to this bacterium occurs when the innate system recognizes common motifs expressed by many pathogens, events driven by pattern recognition receptors like the Toll-like family receptors (TLRs). In this study, lung myeloid-cell populations responsible for the innate immune response (IIR) against S. pneumoniae, and their dependence on the TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 70 publications
(112 reference statements)
1
17
0
Order By: Relevance
“…Inflammatory fibroblasts persistently activate the fibroblasts in an autocrine/paracrine manner in the lungs, resulting in pulmonary fibrosis (63)(64)(65). The proinflammatory role of TLR4-MD2 complex and Myd88 signaling pathway in the lungs has also been evaluated (66)(67)(68)(69) and associated with the fibrotic process leading to pulmonary fibrosis (60,(70)(71)(72)(73)(74). In our study, we found that eCIRP induces proinflammatory cytokines and their pathways in pulmonary fibroblasts in a TLR4 dependent manner.…”
Section: Discussionsupporting
confidence: 54%
“…Inflammatory fibroblasts persistently activate the fibroblasts in an autocrine/paracrine manner in the lungs, resulting in pulmonary fibrosis (63)(64)(65). The proinflammatory role of TLR4-MD2 complex and Myd88 signaling pathway in the lungs has also been evaluated (66)(67)(68)(69) and associated with the fibrotic process leading to pulmonary fibrosis (60,(70)(71)(72)(73)(74). In our study, we found that eCIRP induces proinflammatory cytokines and their pathways in pulmonary fibroblasts in a TLR4 dependent manner.…”
Section: Discussionsupporting
confidence: 54%
“…TLR4 is a key molecule involved in the pathogenesis of inflammatory diseases [ 63 , 64 ]. Indeed, reports on PAMPs recognition mediated by TLR4 strongly support its role against different pathogens, mediating both secretion of proinflammatory cytokines and chemotactic factors that mediate the local recruitment of immune cells, including neutrophils and macrophages [ 46 , 65 , 66 , 67 ]. Additionally, TLR4 recognition of DAMPs in damaged tissues further contributes to local inflammation and fibrosis [ 68 ].…”
Section: Tlr4 Mediated Effectsmentioning
confidence: 99%
“…Upon infection, bone marrow (BM)-derived myeloid cells are produced and then recruited to damaged tissues where they differentiate to dendritic cells and macrophages, contributing to the initial local inflammatory response [ 70 , 71 ]. Additionally, BM-derived monocytes with a patrolling profile are abundant during the late stages of local inflammatory processes and participate in its resolution and tissue repair, but also may produce fibrosis [ 64 , 65 , 71 ]. Alterations in vascular permeability mediated by TLR4 interactions allow infiltration of circulating cells in the injured tissues.…”
Section: Tlr4 Mediated Effectsmentioning
confidence: 99%
“…S. pneumoniae is a gram-positive bacterium that does not express LPS. However, TLR2 and TLR4 recognize lipoteichoic acid, present on its cell wall, and pneumolysin, which it secretes ( Sánchez-Tarjuelo et al., 2020 ). Upon TLR activation, macrophages secrete cytokines to stimulate activation and migration of neutrophils and other immune cells to the site of injury ( Wu et al., 2009 ).…”
Section: Resultsmentioning
confidence: 99%